Physico-chemical characterization and lipid profile of a premix with buriti oil for application in meat products (Research, Society and Development, 2022)
This study aimed to evaluate the physicochemical quality and fatty acid profile of a premix with partial replacement of animal fat by buriti oil (Mauritia flexuosa L.) for use in meat products. Four levels of animal fat replacement by buriti oil were formulated as 0% (P0%) 20% (P20%), 40% (P40%) and 60% (P60%) m/m. The malonic dialdehyde (MDA) content was evaluated by TBARS method, total carotenoids content (µg g-1) by ketone extraction every 30 days during 90 days of storage and fatty acids profile (g 100 g-1 of identified fatty acids) on the day of formulation. The increase in malonic dialdehyde contents (mg of MDA kg-1 of sample) was observed according to the reading times ranging from 0.28 to 0.33 at 30 days, 0.37 to 0.41 at 60 days and 0.53 to 0.75 by 90 days of storage for the formulations. There was a change in the physicochemical characteristics of the premix and improvement for the fatty acid profile in the proportion ω6 and ω3, decrease in the total saturated acids (SFA) content, increase in the oleic acid (ω9) contents according to the substitutions of animal fat for buriti oil. It is concluded that during the period of 90 days of evaluation, the premix with replacement of animal fat by buriti oil (P20%) shows itself as an alternative to be applied in the food industry in meat products such as hamburgers, sausages, meatballs, among others because it decreases the saturated fat content and improves the ω6/ω3 ratio.